Optimization of Microwave Process Conditions for Squid Jerky Using Response Surface Methodology - Joshy, C G; Baby, Tibin G; Parvathy, U; Joseph, Toms C; Remya, S; Bindu, J (Fishery Technology, 2025)
This study successfully optimized the microwave processing conditions—namely microwave power, temperature, and drying time—for producing high-quality squid jerky with desirable moisture content and overall sensory acceptability. A 23 factorial experimental design was formulated, and a first order response regression model with interaction was developed for identifying the optimum microwave process condition with respect to moisture content and sensory attributes. The optimum microwave processing condition was found to be 530W at 60oC with 50 minutes of drying time. Following process optimization, the nutritional profiling and quality evaluation of squid jerky was done with respect to biochemical and microbiological parameters. The histamine content of the squid jerky was found to be within acceptable limits, ensuring food safety. The findings highlight that the optimized microwave process not only improved the nutritional profile but also enhanced the overall quality of the squid jerky, making it a viable method for producing a shelf-stable product.